Effect of Gd2O3 concentration on X-rays induced and photoluminescence characteristics of Eu3+ - Activated Gd2O3–B2O3 glass. (December 2021) - Damdee, B.; Kirdsiri, K.; Kim, H.J.; Yamanoi, K.; Angnanon, A.; Triamnak, N.; Kothan, S.; Kaewkhao, J.
Abstract: Gd 3+ doped borate glass samples with compositions of xGd2 O3 -(99-x)B2 O3 –1Eu2 O3 ; (x = 20, 25, 30 and 35 mol%) (GdBEu) have been synthesized by melt-quenching method at 1400 °C for 3 h. GdBEu glasses characteristics have been determined via FTIR, absorption, emission (X-rays and UV excitation), and CIE color coordinates analysis. The GdBEu glasses presented density increase and molar volume decrease with Gd 3+ ions. Ultraviolet (UV) and X-ray excitation have been indicated performance as well as luminescent properties of Gd2 O3 doped glass structure. The 5 D0 → 7 F0 (582 nm), 5 D0 → 7 F1 (591 nm), 5 D0 → 7 F2 (616 nm), 5 D0 → 7 F3 (654 nm) and 5 D0 → 7 F4 (702 nm) were found at 275 nm and 394 nm excitations. The energy transfer phenomena from Gd 3+ → Eu 3+ in these glasses were observed. Intense reddish-orange emission were observed at 613 nm, which associated by energy transfer phenomena from Gd 3+ → Eu 3+ states in these glasses. The phonon sideband (PSB) and pure electronic transition (PET) were measured and calculated ponon energy of glasses. Decay time of GdBEu luminescence decreased with increase of Gd2 O3 concentration. The Commission Internationale de l'Elcairage (CIE) color coordinates of GdBEu glasses displayed in reddish-orange region. X-rays induced luminescence presented 12% photon emission of GdBEu glasses comparing with BGO scintillation crystal. Highlights: Gadolinium borate binary glasses doped with Eu 3+ ions were synthesized. The emission 5 D0 .→ 7 F0 (582 nm), 7 F1 (591 nm), 7 F2 (616 nm), 7 F3 (654 nm) and 7 F4 (702 nm) observed. Phonon sideband observed for Gadolinium borate binary glasses doped with Eu 3+ glasses. Decay time of GdBEu luminescence decreased with increase of Gd2 O3 .